A Postcolonial Study of the Socio-Political Scenarios in Twilight in Delhi and The Murder of Aziz Khan - Bashir, Saima; Hussain, Jafar (Annals of Human and Social Sciences, 2025)
Based on an interpretative reading of Ahmad Ali’s Twilight in Delhi (1940) and Zulfikar Ghose’s The Murder of Aziz Khan (1967), this article conducts a comparative analysis of the socio-political scenarios in pre- and post-independence societies of India and Pakistan. Twilight in Delhi explores the legacy of colonialism and Partition’s repercussions, while Murder of Aziz Khan critiques Pakistan’s managerial shortcomings and lack of ambition. Employing qualitative research methods and conceptual frameworks from Edward Said, Homi Bhabha, and Gayatri Spivak, the study provides deep insights into familial ties, social complexities, and political influences that shape individual identities. In addressing these challenges, the paper proposes integrating cultural education and policy reform initiatives to reconcile historical legacies with contemporary governance. This approach offers a pathway toward healing and the evolution of identity in formerly colonized and neo-colonized societies. Ultimately, these strategies aim to foster a more inclusive future, significantly mitigating lingering historical effects.